Gut Microbial Translocation in Critically Ill Children and Effects of Supplementation with Pre- and Pro Biotics. (15th August 2012) - Papoff, Paola; Ceccarelli, Giancarlo; d'Ettorre, Gabriella; Cerasaro, Carla; Caresta, Elena; Midulla, Fabio; Moretti, Corrado
Abstract : Bacterial translocation as a direct cause of sepsis is an attractive hypothesis that presupposes that in specific situations bacteria cross the intestinal barrier, enter the systemic circulation, and cause a systemic inflammatory response syndrome. Critically ill children are at increased risk for bacterial translocation, particularly in the early postnatal age. Predisposing factors include intestinal obstruction, obstructive jaundice, intra-abdominal hypertension, intestinal ischemia/reperfusion injury and secondary ileus, and immaturity of the intestinal barrier per se. Despite good evidence from experimental studies to support the theory of bacterial translocation as a cause of sepsis, there is little evidence in human studies to confirm that translocation is directly correlated to bloodstream infections in critically ill children. This paper provides an overview of the gut microflora and its significance, a focus on the mechanisms employed by bacteria to gain access to the systemic circulation, and how critical illness creates a hostile environment in the gut and alters the microflora favoring the growth of pathogens that promote bacterial translocation. It also covers treatment with pre- and pro biotics during critical illness to restore the balance of microbial communities in a beneficial way with positive effects on intestinal permeability and bacterial translocation.